Evaluation of the accuracy of Lachman and Anterior Drawer Tests with KT1000 ın the follow-up of anterior cruciate ligament surgery - Kilinc, Bekir Eray (J Exerc Rehabil, 2016)
Ligament laxity measurement is clinically valuable to diagnose the injury and also to compare the laxity before and after surgical procedure. The aim of the study was to compare the accuracy of the Lachman and Anterior Drawer Tests to evaluate the knee examination with the KT1000 arthrometer after the anterior cruciate ligament (ACL) surgery in early follow-up period. Fourty ACL reconstructed knees were examined with the Lachman and Anterior Drawer Tests, and KT1000 arthrometer with compariable intact knee of the same patients. Physical emanination findings were compared with the KT1000 arthrometer with each power. Spearman correlation and receiver operating characteristic (ROC) analysis were used for the evaluation of relations between parameters. Significance was evaluated in P<0.1 and P<0.05. The mean age was 28.18±6.21 yr, and the mean follow-up was 23.09±9.08 months. The mean KT1000 measurements of 40 operated knees state at 6.8, 9.1, 13.6 kg and maxium anterior displacement forces were 4.9, 6.7, 8.7, and 11.9 mm, respectively. The same values for the same acting forces of intact knees were 4.2, 5.9, 7.8, and 10.2, respectively. In Spearman’s correlation and ROC analysis at 13.6-kg power on KT1000 arthrometer statistically matched with pyhsical examinations (P<0.1, P<0.01). In our study, correlation of physical examinations with KT1000 arthrometer is a worthy evaluation technique that can be added to examination of ACL reconstructed knee to control with inexperinced examiners’ findings. We suggest that at 13.6-kg power with KT1000 arthrometer findings perfectly match the Lachman and Anterior Drawer Tests of the knee.